The IFS Scottish Budget Report: 2024-2025 - Bee Boileau; Kate Ogden; David Phillips; Sam Ray-Chaudhuri; Madeline Thomas; Max Warner; Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2024)
The Scottish Government's Budget for 2024-25 takes place at a time of particular uncertainty about the future funding environment. UK government spending plans both for the coming year and for later years seem likely to be topped up, but when and by how much is unclear. The current UK government wants to announce tax cuts before the upcoming general election, but history tells us that we should not be surprised if taxes were to rise post-election. And the performance of Scotland's devolved tax revenues - in particular given recent and planned tax policy changes - is uncertain. Taken together, these factors make the task of planning Scottish tax and spending decisions particularly challenging - an issue discussed in an IFS comment published alongside this report (Phillips, 2024).
Keywords: 330; Education and skills; Government finances and spending; Health and social care; Taxes and benefits; Scottish Budget 2024-25; Devolved government finances; Education; Higher education; Scotland; COVID-19; Health; Healthcare; NHS; Productivity; Distributional effects; Government spending; Income taxes; Local government finance; Property taxes; Public finance; Public sector; Tax; Working age benefits